Pemanfaatan Botol Plastik Bekas Sebagai Wadah Dalam Sistem Hidroponik Untuk Budidaya Sayuran - Wahyu Halya Aprilia Putri; Renita Dwi Lestari; Prasmita Dian Wijayanti (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2024)
The residents of RW 05 Jomblang, Candisari District, Semarang City, are increasingly concerned about the impact of plastic waste on the environment. As a solution, used plastic bottles are being utilized as planting media in hydroponic techniques by MBKM students from various universities, such as UPN "Veteran" East Java, Padjadjaran University, and Semarang State University. This utilization of plastic bottles reduces waste while supporting sustainable agriculture by minimizing the use of land and water. The program raises community awareness about eco-friendly urban farming, focusing on water efficiency and quick harvesting processes. Education includes basic hydroponic techniques and their implementation using used bottles, which has been met with active community participation. Evaluations show tangible results, such as pakcoy plants being distributed to participants. Discussions with the RW 05 Chairman reveal significant benefits for the community in utilizing used items for agriculture. This program strengthens the community and suggests further development to enhance local food security and environmental awareness, as well as motivate the adoption of modern agricultural technologies